Taxon-free ecomorphological analysis of fossil bovids from the Sterkfontein and Swartkrans deposits, South Africa - Sambo, Recognise (My University, 2020)
Sterkfontein and Swartkrans caves (1 km apart) are situated in the Cradle of Humankind World Heritage Site, Gauteng, South Africa. The two sites hold records of the two Earlier Stone Age tool technologies (Oldowan and Acheulean), and have yielded significant fossil hominins in southern Africa that span the late Pliocene and early Pleistocene period. This is the first study in the Cradle which applies a ‘taxon-free’ ecomorphological approach to investigates palaeoenvironmental changes at Sterkfontein and Swartkrans caves between 2.8 and 1.5 Ma through the functional morphology of well-preserved bovid astragali. Seven measurements were taken on 55 bovid astragali following methods employed by previous studies. A Discriminant Function Analysis (DFA) was conducted to compare morphologies of unknown fossil bovids astragali from these two sites to published modern bovid astragali of known ecological adaptations (e.g., open cover, light cover, heavy cover, forest). Results show that morphologically, bovids from the two sites are adapted to a mosaic of habitats. Bovids from Sterkfontein Member 4 (STK-M4) ~2.8-2.4 Ma manoeuvered in less complex environmental settings such as open plains, grasslands, tall grasses, light bushes, as well as medium density heavy cover environments (e.g., bushlands, woodlands), and a riparian forest. Similar environmental conditions persisted to the time of Sterkfontein Member 5 East, Oldowan infill (STK-M5E) ~2.18 Ma although with more tree cover. In contrast, the environment at Swartkrans during the deposition of Member 1 Lower Bank, Oldowan (SKX-M1 LB) ~ 2.2 Ma was favourable to bovids adapted to light cover, moderate open cover and forest habitats with no heavy cover. The same conditions are evident during Swartkrans Member 2, Acheulean (SKX-M2) times ~1.5 Ma but it seems the environment was opening up more. These results suggest a time transgressive trend from medium density heavy cover and forest environments to more light cover and open environments associated with the expansion of grasslands between ca. 2.8 Ma to 1.5 Ma at the two sites. This fits well with the broader reconstructions of palaeoclimatic change in Africa and in the Cradle, which suggest drying trends resulting in more varied and open environments during the Plio-Pleistocene onwards
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, 2020
Keywords: Paleontology; Ecology